Nuclear disasters and displacement - Meybatyan, S (Refugee Studies Centre, University of Oxford, 2014)
The lessons of the Fukushima nuclear accident in 2011 seem to be the same as those from Chernobyl 25 years earlier, despite the different political settings. Apparently not much had been learned.